Potentially meaningful teaching unit with the transversal theme Traffic Education for the teaching of kinematics in sciences - Ledur, José Ricardo (Seven Editora, 2024)
The work presents the results of a Potentially Significant Teaching Unit (UEPS), with the transversal theme "Traffic Education", applied in a ninth grade class of Elementary School. This work derives from a qualitative research whose objective was to verify the potential of a LIFO in promoting meaningful learning of Kinematics contents. The materials and stages of the LIFO were grounded in the Theory of Meaningful Learning. The evaluation conducted during the UEPS had a formative character, as there was a follow-up of the students in the accomplishment of tasks in the different stages. The data from several evaluative instruments were analyzed by means of descriptive statistics and Discursive Textual Analysis. The analysis showed that the objective of this work was achieved, as there were advances in the understanding of Kinematics concepts and favored the improvement of students’ attitudes to deal more adequately with the complexity of the "Traffic" phenomenon. The study showed that the use of this transversal theme produced relevant relationships for learning, contributing to new ways of teaching and learning Science. This proposal was, therefore, a material that can be qualified with potential for the development of meaningful learning. DOI:https://doi.org/10.56238/sevened2024.007-002